beta-(1 -> 3,1 -> 6)-D-glucans produced by Diaporthe sp endophytes: Purification, chemical characterization and antiproliferative activity against MCF-7 and HepG2-C3A cells - Orlandelli, Ravely Casarotti; Corradi da Silva, Maria de Lourdes [UNESP]; Dalberto Vasconcelos, Ana Flora [UNESP]; Almeida, Igor Vivian; Pimenta Vicentini, Veronica Elisa; Prieto, Alicia; Diaz Hernandez, Maria Dolores; Azevedo, Joao Lucio; Pamphile, Joao Alencar (Elsevier B.V., 2017)
This study reports the characterization and antiproliferative activity of exopolysaccharides (EPS) produced by submerged cultures of the endophytes Diaporthe sp. JF766998 and Diaporthe sp. JF767007 isolated from the medicinal plant Piper hispidum Sw. Both strains secreted a crude EPS that, upon size exclusion chromatography, showed to contain a heteropolysaccharide (galactose, glucose and mannose) and a high-molecular weight glucan. Data from methylation analysis, FTIR and NMR spectroscopy (H-1, COSY, TOCSY and HSQC-DEPT) indicated that the purified glucan consisted of a main chain of glucopyranosyl beta-(1 -> 3) linkages substituted at 0-6 by glucosyl residues. According to MIT assay, some treatments of both beta-glucans have antiproliferative activity against human breast carcinoma (MCF-7) and hepatocellular carcinoma (HepG2-C3A) cells after 24 and 48 h of treatment, exhibiting a degree of inhibition ratio that reached the highest values at 400 mu g/mL: 58.0% (24h) and 74.6% (48 h) for MCF-7 cells, and 61.0% (24 h) and 83.3% (48 h) for HepG2-C3A cells. These results represent the first reports on the characterization and antiproliferative effect of beta-glucans from Diaporthe species and also expand the knowledge about bioactive polysaccharides from endophytic sources. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Endophytic fungi; Exopolysaccharide; MTT assay; Spectroscopic analysis